Carotid Artery Stenting Improves Cerebral Hemodynamics Regardless of the Flow Direction of Ophthalmic Artery. (February 2015) - Liu, Chi-Hung; Chang, Chien-Hung; Chang, Ting-Yu; Huang, Kuo-Lun; Lin, Jr-Rung; Chen, Yu-Wei; Yip, Bak-Sau; Ryu, Shan-Jin; Chang, Yeu-Jhy; Lee, Tsong-Hai
We enrolled 221 patients with elective carotid artery stenting (CAS). Patients with contralateral carotid stenosis exceeding 50%, insufficient vertebral artery (VA) flows, or angioplasty at subclavian artery were excluded. All patients underwent serial cerebral ultrasound studies. Of the 116 included patients, the direction of ophthalmic artery (OA) flow was forward in 74 patients while reversed in 42. The reversed flow group had worse ipsilateral stenosis, higher hemoglobin, and cardiac output. After CAS, the reversed flow group had an immediate recovery of ipsilateral internal carotid artery flow volume (FV; P < .0001), time average velocity (TAV) of middle cerebral artery ( P = .02), and normalization of OA flow. The forward flow group had gradual decrement in TAV of contralateral anterior cerebral artery ( P = .01) and total FV of VA ( P = .001). Our results suggest CAS improves cerebral hemodynamics through different ways regardless of the direction of OA flow.